THE RELATIONSHIP BETWEEN LOW BIRTH WEIGHT WITH PNEUMONIA TODDLERS IN WEST JAVA - Wahyu Dyah Sukmawati (Jurnal Berkala Epidemiologi, 2019)
Background: West Java Province is the region with the highest number of pneumonia toddlers and mortality in toddlers due to third highest number of mortality in Indonesia at 2017. One of the risk factors for pneumonia toddlers was low birth weight (LBW). Purpose: This study has purpose to analyze the correlation between low birth weight with pneumonia toddlers in West Java Province at 2017. Methods: Type of this study was an observational type study with correlation study design. This study used secondary data from publication Health Profile of West Java Province in 2017. The population was all toddlers who suffered pneumonia from 18 districts and 9 cities in West Java Province. The independent variable was the coverage of low birth weight babies, while the dependent variable was the coverage of the discovery of pneumonia in toddlers. The study used data analysis through Durbin Watson test and Pearson correlation test. Results: This study showed there was a significant correlation between low birth weight with pneumonia toddlers with p value= 0,01 (p < 0,05). Strength of correlation showed there were moderate relationship and positive direction (pearson correlation = 0,54). so that it can be interpreted that the higher the events of low birth weight babies, then the higher the events of pneumonia in toddlers, and vice versa. Conclusion: There was a significant correlation between low birth weight with pneumonia toddlers in West Java Province in 2017.